Foreign direct investment and regional economic development. (2017) - Mahalakshmi, S.; Thiyagarajan, S.; Naresh, G.
Foreign direct investment is assumed to be one of the important conditions paving way for improving the competitiveness and managerial skills of the economy which in turn increases production, exports, employment and wages. Therefore, an attempt has been made to determine the contribution of FDI inflows on the development of Indian states. The effect of FDI inflows on state development indicators have been identified by applying panel fixed effects model based on the assumption that the intercept as well as slope coefficients vary over individual cross sections/states. The results states that FDI inflow has not significantly contributed in increasing the economic development of most of the Indian states except few. It could be mainly because large volume of FDI inflows are in the form of brown field investment and moreover, it has been attracted by very few major states which possess better infrastructure and potential human resource.